How does participation and browsing affect continuance intention in virtual communities? An integration of curiosity theory and subjective well-being. Issue 3 (17th February 2021) - Fang, Yu-Hui; Li, Chia-Ying; Arain, Ghulam Ali; Bhatti, Zeeshan Ahmed
ABSTRACT: Based on theories about curiosity and subjective well-being (SWB), this study proposes a research model for how participation and browsing initiate different routes to satisfying members' diverse needs, thus increasing their SWB and their continuance intention in knowledge-based virtual communities (VCs). Two curiosity constructs, informational deprivation epistemic curiosity (D-EC) and interest-type epistemic curiosity (I-EC), moderate the wanting route and liking route, respectively. The research model is tested with data from 476 members of one knowledge-based VC using a web survey. Results show that member participation stimulates the wanting route to satisfaction by activating the need for reflective learning and uncertainty reduction, whereas browsing stimulates the liking route to member satisfaction by eliciting enjoyment. Both routes thus increase member SWB and, ultimately, continuance intention. Along the wanting route, D-EC reinforces relationships related to reflective learning but attenuates those related to uncertainty. I-EC alleviates the relationships along the liking route. Comparisons of the relative importance of hypothesised relationships between participants and lurkers indicate that participants feel more satisfied with knowledge sharing, enjoy greater SWB, and maintain higher continuance intention than lurkers. These results can therefore help managers of VCs leverage learning- or fun-oriented mechanisms, depending on member curiosity type.